2020
DOI: 10.1002/nur.22087
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond the measure: Understanding patients' experiences of communication with nurses

Abstract: Under Medicare's Value-Based Purchasing Program, scores derived from the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey are used in the determination of incentive payments and financial penalties for healthcare organizations. Organizations, therefore, invest in approaches to improve the likelihood of positive patient responses. Evidence suggests that nurse communication as measured by HCAHPS influences overall patient satisfaction, yet little is known regarding what patients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
(60 reference statements)
1
2
0
Order By: Relevance
“…In addition to the abovementioned characteristics, the professional's ability to listen attentively, sensitively, with time and a welcoming and respectful behavior stands out in order to encourage the patient to participate in their care. This is imilar to the findings of another study in which these skills are identified as factors that favor establishing a trusting relationship between patient and professional 19 and empathetic communication, anticipating the patient's needs and positively influencing patient satisfaction 20 .…”
Section: Discussionsupporting
confidence: 82%
“…In addition to the abovementioned characteristics, the professional's ability to listen attentively, sensitively, with time and a welcoming and respectful behavior stands out in order to encourage the patient to participate in their care. This is imilar to the findings of another study in which these skills are identified as factors that favor establishing a trusting relationship between patient and professional 19 and empathetic communication, anticipating the patient's needs and positively influencing patient satisfaction 20 .…”
Section: Discussionsupporting
confidence: 82%
“…The importance for patients to have a dialogue with the nurses must not be underestimated [ 37 ]. The patients in this study were not systematically involved in the decisions making regarding their nutritional care as the nursing staff perceived this as time‐consuming, which contrasts with the patients' call for nurses to respond to the patients' needs [ 38 ]. Communication that acknowledges the patient's role in care planning can make the difference in avoiding inadequate or missing care [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sitting with patients allows nurses to explain the plan of care and address concerns while improving the patient's perception of the nurse's communication 6,8-11,15. Sitting versus standing when talking with patients is also perceived as spending more time with the patient; in fact, patients overestimated the time the clinician was in the room when sitting 8,14,16,17. Sitting not only affects the perception of time but also increases patient satisfaction scores and builds trust for an effective therapeutic relationship between the nurse and the patients 4,7,10-12,14,18…”
Section: Literature Reviewmentioning
confidence: 99%